To the Problem of Classification of Information Sources of the Historical and Pedagogical Research - Petrenko, Oksana (Pedagogical Discourse, 2013)
In the article the author studies the problem of classification of information sources of the historical and pedagogical research. The criteria that scientists choose to group source base of historical and pedagogical research have been analyzed, that is territorial and regional features – sources belonging to a particular culture, the level of synthesis of information, taking into account aspects of the information contained in the source and the typical criteria for sources differentiated in terms of sign systems that authors use; temporal, chronological criteria; subject of study criteria (sources learning personalities, scientific schools, pedagogical trends, of the individual schools). A theoretical understanding that historical source (the product of culture, objected result of human activity) acts as a single object of various historical and pedagogical researches in a variety of their subject and considering certain criteria makes it possible to distinguish the relevant sources of learning the history of pedagogy, that will be the foundation for the analysis of the researcher within this or that problem in the history of pedagogy.